The Representation of Lakes as Traces of Curses and Punishments in Indonesia Folklore: An Ecocritical Study - Rahma Nurul Aini; Wachid Eko Purwanto (JENTERA: Jurnal Kajian Sastra, 2026)
This study is motivated by the existence of folktales about the origins of lakes in the Indonesian archipelago, which not only explain geographical phenomena but also represent the relationship between human behavior and environmental change as a consequence of violations of moral and social values. This study aims to uncover narratives of curses and punishments in the folktales of lakes in the Indonesian archipelago through an ecocritical literary approach using six concepts from Garrard (2012) namely pollution, wilderness, apocalypse, dwelling, animals, and earth. The study employs a qualitative descriptive method with data consisting of seven folktales: The Origin of Lake Toba, Lake Laut Tawar, Lau Kawar, Lake Maninjau, The Legend of Bulalo La Limutu, Telaga Warna, and Lake Tes. The results of the study indicate that lakes in folk tales are not merely interpreted as moral consequences of human actions but also represent ecological responses to the disruption of environmental balance and function as new ecological spaces that sustain the social and economic lives of surrounding communities. Furthermore, folklore serves as a pedagogical device that instills moral values, social norms, and ecological awareness, emphasizing that humans are part of nature, not its rulers (anthropocentric). Abstrak Penelitian ini dilatarbelakangi oleh keberadaan cerita rakyat asal-usul danau di Nusantara yang tidak hanya menjelaskan fenomena geografis, tetapi juga merepresentasikan hubungan antara perilaku manusia dan perubahan lingkungan sebagai konsekuensi pelanggaran nilai moral dan sosial. Penelitian ini bertujuan mengungkap narasi kutukan dan hukuman dalam cerita rakyat danau di Nusantara melalui pendekatan ekokritik sastra menggunakan enam konsep Garrard (2012), yaitu pollution, wilderness, apocalypse, dwelling, animals, dan earth. Penelitian menggunakan metode deskriptif kualitatif dengan data berupa tujuh cerita rakyat, yaitu Asal-Usul Danau Toba, Danau Laut Tawar, Lau Kawar, Danau Maninjau, Legenda Bulalo La Limutu, Telaga Warna, dan Danau Tes. Hasil penelitian menunjukkan bahwa danau dalam cerita rakyat tidak hanya dimaknai sebagai konsekuensi moral atas tindakan manusia, tetapi juga merepresentasikan respons ekologis terhadap terganggunya keseimbangan lingkungan serta berfungsi sebagai ruang ekologis baru yang menopang kehidupan sosial dan ekonomi masyarakat di sekitarnya. Selain itu, cerita rakyat berfungsi sebagai sarana pendidikan (pedagogical device) yang menanamkan nilai moral, norma sosial, serta kesadaran ekologis bahwa manusia merupakan bagian dari alam, bukan penguasa alam (anthropocentric).